A Strategy for Polysulfides/Polyselenides Protection Based on Co9S8@SiO2/C Host in Na‐SeS2 Batteries. (13th May 2020) - Yang, Tingting; Qi, Yuruo; Zhong, Wei; Tao, Mengli; Guo, Bingshu; Wu, Yuanke; Bao, Shu‐Juan; Xu, Maowen
Abstract: To obtain unbroken sulfides with delicate morphology from metal–organic frameworks (MOFs), a method for in situ growth of SiO2 protective layers on the surface of MOFs is proposed. This strategy can be successfully expanded to a variety of MOFs (ZIF‐67, Cu‐MOF, ZIF‐8, and PBA). Importantly, room‐temperature Na‐SeS2 batteries with Co9 S8 @SiO2 /C prepared from ZIF‐67 as cathode host are assembled. Due to the hollow structure that can relieve the volume expansion and the co‐adsorption of sodium polysulfides/sodium polyselenides by Co9 S8 @SiO2 /C, the SeS2 /Co9 S8 @SiO2 /C cathode shows excellent rate performance and Coulombic efficiency. In addition, ex situ X‐ray diffraction and in situ Raman results show that S8 and Se8 are generated after the discharge of SeS2, and Se8 is preferentially oxidized during charging. Abstract : A simple, effective, general strategy for the preparation of intact sulfide‐based hollow structures from metal–organic frameworks is presented. Benefiting from the structural and compositional advantages, the SeS2 /Co9 S8 @SiO2 /C composite cathode shows excellent electrochemical performance.